The Influence Of Field Work Practice Experience And Task Commitmenton Students' Career Readiness At State Vocational School 3 Bitung - Alfiani Tooy; Henny N. Tambingon; Deitje A. Katuuk (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
Abstract This study aims to examine the effect of internship experience and task commitment on students' career readiness. This research employed a quantitative approach using multiple linear regression analysis. The population of this study consisted of students of SMK Negeri 3 Bitung, with a sample of 36 respondents. The variables examined in this research include Internship Experience (X1), Task Commitment (X2), and Career Readiness (Y). Data were collected through questionnaires and analyzed using validity tests, reliability tests, descriptive statistics, classical assumption tests, and hypothesis testing, including the Pearson Product Moment correlation test, t-test, F-test, and coefficient of determination. The results indicate that internship experience and task commitment have a positive relationship with students' career readiness. The regression analysis shows that internship experience has a significant effect on career readiness with a significant value of 0.002 < 0.05, while task commitment also has a significant effect on career readiness with a significant value of 0.020 < 0.05. Simultaneously, internship experience and task commitment significantly influence career readiness with a significant value of 0.001 < 0.05 and a coefficient of determination of 0.498, which means that both variables explain 49.8% of the variance in career readiness. Keywords: internship experience, task commitment, students' career readiness